1995
DOI: 10.1016/s0022-5223(95)70251-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implantable cardioverter-defibrillators on mortality among patients on the waiting list for heart transplantation

Abstract: Implantable cardioverter-defibrillators were investigated for their impact on mortality in 228 consecutive heart transplant candidates on the waiting list for transplantation (207 patients without and 21 with implantable cardioverter-defibrillator therapy). The mortality rate in 207 patients without implantable cardioverter-defibrillator therapy was 23.2% and in 21 patients with implantable cardioverter-defibrillator therapy was 4.7%. In a Cox proportional hazards model for all 228 study patients (mortality wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…In a retrospective analysis, Sweeney et al 21 found that ICD therapy in patients on the waiting list for cardiac transplantation (nϭ32) improved neither overall nor sudden death-free survival compared with patients with or without antiarrhythmic drug treatment. Grimm et al 22 analyzed the influence of ICD therapy on mortality in 228 consecutive patients on the waiting list for cardiac transplantation. They demonstrated a survival benefit of ICD therapy for selected patient subgroups of survivors of sudden cardiac death and patients with high-grade ventricular arrhythmias on Holter ECG.…”
Section: I-174 Circulation September 18 2001mentioning
confidence: 99%
“…In a retrospective analysis, Sweeney et al 21 found that ICD therapy in patients on the waiting list for cardiac transplantation (nϭ32) improved neither overall nor sudden death-free survival compared with patients with or without antiarrhythmic drug treatment. Grimm et al 22 analyzed the influence of ICD therapy on mortality in 228 consecutive patients on the waiting list for cardiac transplantation. They demonstrated a survival benefit of ICD therapy for selected patient subgroups of survivors of sudden cardiac death and patients with high-grade ventricular arrhythmias on Holter ECG.…”
Section: I-174 Circulation September 18 2001mentioning
confidence: 99%
“…statistically significant survival benefit. 24 This contradicts more recent studies demonstrating improved outcomes for ICDs implanted for both primary and secondary prevention. In a multicenter study with 1089 patients, the survival benefit was actually more pronounced in patients who received an ICD for primary prevention vs the non-ICD group (88% vs 67%, P , .0001) as compared to secondary prevention vs the non-ICD group (77% vs 67%, P 5 .01).…”
Section: Survival Benefit Of Icd Implantation In Patients Awaiting Htmentioning
confidence: 90%
“…As a result the ICD has been proposed to avoid sudden death in patients who could otherwise expect prolonged survival following transplantation. A recent study has shown benefit in implanting defibrillators in patients with life‐threatening ventricular tachyarrhythmias awaiting transplantation . However, the hypothesis that prophylactic ICD implantation in all patients as a ‘bridge’ to transplantation will result in significant survival benefit remains to be proven in a prospective trial.…”
Section: Secondary Prevention Of Life‐threatening Ventricular Tacymentioning
confidence: 99%